Health promotion innovation in primary health care - McManus, Alexandra (Australasian Medical Journal Pty Ltd, 2013)
Previously, the main focus of primary health care practices was to diagnose and treat patients. The identification of risk factors for disease and the prevention of chronic conditions have become a part of everyday practice. This paper provides an argument for training primary health care (PHC) practitioners in health promotion, while encouraging them to embrace innovation within their practice to streamline the treatment process and improve patient outcomes. Electronic modes of communication, education and training are now commonplace in many medical practices. The PHC sector has a small window of opportunity in which to become leaders within the current model of continuity of care by establishing their role as innovators in the prevention, treatment and management of disease. Not only will this make their own jobs easier, it has the potential to significantly impact patient outcomes.